The effect of priming and priming time on germination and some biochemical traits of Camelina (Camelina sativa) Sohail cultivar under drought stress - Mehdi Razmkhah; Ali Moradi; Hojatollah Latifmanesh; Hamidreza Balouchi (علوم و فناوری بذر ایران, 2025)
Camelina (Camelina sativa) is a one-year oil plant, one of the most important problems of its cultivation is the interaction of seed germination and seed establishment with drought stress. Use of herbal treatments such as rye plant extract can speed up them, especially in drought-stress conditions. Therefore, this research was conducted to investigate the effect of priming and priming time on germination and some biochemical traits of Camelina under drought stress in the Agriculture and Genetics Laboratory of Yasouj University from 2021 to 2022. The experiment was conducted as a factorial in a completely randomized design with 4 replications. The first factor was priming with Danko variety of rye plant root extract at 3 levels (zero, 40 and 60%), The second factor was priming times at three levels (zero, 6 and 12 hours) and the third factor included drought stress at three levels (zero, -3 and -6 times). Based on the obtained results, it was observed that drought stress affected the biochemical indicators and germination of Camelina and pre-treatment with rye extract at a concentration of 60% along with prime in 12 hours with the improvement of some biochemical indicators and germination were able to increase the tolerance of Camelina seedlings under drought stress by affecting the non-enzymatic antioxidant defense system of the plant. The results of the experiment show that using Danko variety of rye root extract with a concentration of 60% in 12 hours improves physical characteristics of the seed, helping germination in optimal and drought stress conditions.